ANALISIS KUALITAS SDM DAN AKSES PERMODALAN TERHADAP KINERJA KEUANGAN UMKM KULINER DI KOTA BENGKULU - kurniawan, Kiemas; Effendi, Yanto (Program Studi Manajemen Keuangan Syariah, 2025)
The purpose of this study is to see the influence of human resource quality and access to capital on the financial performance of UMKM kuliner in Bengkulu City. The quality of human resources with a t-value of 1.674 with a significance level of 0.006 is > 0.05 which means there is a significant influence of human resource quality on the financial performance of culinary UMKM Kuliner in Bengkulu City with a coefficient value of 0.218, this also shows that the quality of human resources on the financial performance of UMKM kuliner in Bengkulu City has a low and positive influence. Access to capital on the financial performance of UMKM kuliner in Bengkulu City with a t-value of 2.546 and a significance level of 0.002 is <0.05, a regression coefficient value of 0.249 is obtained. Simultaneously or together shows an F-value of 1461.331 with a significance level of <0.003, this proves that simultaneously there is an influence of the variables of human resource quality, access to capital on the financial performance of UMKM kuliner in Bengkulu City